Sucrose feeding in mouse pregnancy leads to hypertension, and sex-linked obesity and insulin resistance in female offspring - Samuelsson, Anne-Maj; Matthews, Phillippa A.; Jansen, Eugene; Taylor, Paul D.; Poston, Lucilla (Frontiers in Physiology, 2013)
Eating an unbalanced diet during pregnancy may induce long-term health consequences in offspring, in particular obesity, insulin resistance and hypertension. We tested the hypothesis that a maternal diet rich in simple sugars predispose mouse offspring to obesity, glucose intolerance and cardiovascular diseases in adulthood. Female C57BL/6J mice were fed either a standard chow or a sucrose-rich diet (26% of total energy) 6 weeks prior to mating, throughout pregnancy and lactation. Offspring of control dams (OC) and high sucrose fed dams (OSF) were weaned onto standard control chow, and metabolic and cardiovascular parameters determined at 3 months of age. Both male and female OSF were hyperphagic by 4 weeks of age and females were heavier than OC at 9 weeks. At 3 months, female OSF showed a significant increase in inguinal fat pad mass, whereas skeletal muscle mass (tibialis anterior) and locomotor activity were decreased relative to OC. A ten-fold increase in fasting serum insulin in female OSF versus OC at 3 months (Insulin [pmol/L] mean±SEM, OSF, 200.3±16.1, versus OC, 20.3±1.8, n=6 P<0.001), was associated with impaired glucose tolerance (AUC [mmol/L min] mean±SEM, OSF 1437.4±124.2 versus OC, 1076.8±83.9, n=6, P<0.05). Both male and female OSF were hypertensive as assessed by radiotelemetry (night-time systolic arterial pressure [mmHg] mean±SEM, male OSF, 128±1 versus OC, 109±1, n=6, P<0.01; female OSF, 130±1 versus OC, 118±1, n=6, P<0.05). Analysis of heart rate variability demonstrated an increased low:high frequency ratio in male and female OSF (P<0.05), indicative of heightened sympathetic efferent tone. Renal tissue noradrenaline content was markely raised in the OSF versus OC (noradrenaline [pg/ml/mg tissue] mean±SEM, male OSF, 2.28±0.19 versus OC 0.84±0.09, n=6, P<0.01) . Exposure to a maternal diet rich in sucrose led to obesity and glucose intolerance in female mice offspring, and hypertension in both sexes.